Building a Competitive Edge: The Effectiveness of the 3 in 1 Program in Enhancing LPK Kartika's Marketing - Yohana Efenia Ndruru; Ray Octafian (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
The Kartika Job Training Institute (LPK) and STIEPARI Semarang have formed a partnership to offer part-time classes at the Kartika LPK building on weekends, allowing students to balance their employment commitments. Nevertheless, a number of obstacles have arisen, including the necessity for students to efficiently handle their time and focus, while simultaneously fulfilling their obligations to both endeavours. The data collection methods employed in this study encompassed interviews conducted by the interviewer, direct observations of the study subject, and a comprehensive literature review that entailed gathering information from newspaper articles, books, and prior scholarly research. The research findings, acquired through various data collection approaches, illustrate the efficacy of utilising Kartika LPK's advantages to capitalise on current chances. This entails the creation of distinctive and varied products in order to appeal to a more devoted client demographic, as well as the efficient utilisation of technology to bolster the advancement of the 3 In 1 programme. Moreover, effectiveness is attained by capitalising on existing possibilities to overcome hurdles. Ultimately, the achievement of lowering dangers is accomplished by means of proficient communication among training participants, enhanced customer service, and more streamlined employee training.